Placental changes in hypertensive pregnancy: a comparison with normotensive pregnancy - Chhatwal, Jashan; Chaudhary, Dev Nanda; Chauhan, Neena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive pregnancy may be responsible for vascular damage, enhanced systemic inflammation and insulin resistance in the placenta as oxygen and nutrient transfer is impaired and oxidative stress is generated affecting the placental growth and development. Placental growth pattern in hypertensive pregnancies shows a variable pattern owing to placental insufficiency. Present study was done to investigate the morphological and histological changes in placenta in hypertensive pregnancy. Methods: A total of 42 pregnant women with hypertensive disorder with gestational age 28-42 weeks and singleton pregnancy were enrolled as cases in the study. A total of 42 matched normotensive pregnant women were enrolled as controls. All the women were followed up till delivery. At delivery, placental specimen were collected and assessed for morphological, morphometric and histological changes. Findings were compared with normotensives. Data was compared using Independent sample’s ‘t’-test and Chi-square test. Results: Mean age of cases was 27.60±4.37 years, majority were gravida 1/2 (66.7%), 45.2% had moderate to severe edema, 50% had urinary albumin levels >100 mg/dl. A total of 8 (19.0%) had gestational hypertension, 16 (38.1%) had preeclampsia, 10 (23.8%) had severe preeclampsia and 8 (19.0%) had eclampsia. Mean placental weight and diameter of cases was significantly higher than that of control group. Mean placental thickness was also higher but difference was not significant statistically. Calcification, infarction and hematoma were seen in 45.2%, 16.7% and 11.9% of cases as compared to 28.6%, 4.97% and 0% of controls. Histologically, syncytial knots, cytotrophoblastic cellular proliferation, hyalinized area, proliferation of medium sized blood vessels, stromal fibrosis and fibrinoid necrosis in significantly higher proportion of cass as compared to controls (p<0.05). Mean fetoplacental ratio was 5.01±0.99 and 5.24±0.61 in controls (p=0.195). Conclusions: Hypertension during pregnancy affects the placental growth and development.